Capacity for development : new solutions to old problems - Fukuda-Parr, Sakiko, 1950-; Lopes, Carlos; Malik, Khalid, 1952- (Earthscan Publications, 2002)
Leading experts consider how development programmes can increase the levels of knowledge, skill, technical know-how and productive capacity of populations in the South. The volume is organized into three parts on ownership, institutional capital and knowledge networks. They explore the participatory empowerment that builds capacity, a framework enabling social forces to contribute, and a paradigm of knowledge in the network age. The result shows how, in future, capacity development through technical co-operation can be successfully pursued.